Hyperborea and Heteronomy—Pro et Contra (“Personal” Poetics of Branislav Matić) - Jeftimijević Mihajlović, Marija S. (Collection of Papers of the Faculty of Philosophy in Priština, 2026)
Branislav Matić, a poet of refined sensitivity, author, publicist, and editor of numerous publications, with his first poetry collection Hyperborean Chronicle (2015), published in his mature years, emphasized the importance of returning to the ancient (spiritual) heritage of humanity. Drawing primarily on the teachings of the Hungarian thinker Béla Hamvas, as well as on ancient Hindu metaphysics, Matić constructed a distinctive poetic–philosophical system, founded on the principle of “spiritualizing nature and deifying man.” Following the example of his spiritual teacher Hamvas, in our age of “modern barbarism,” Matić highlights the vocation of the poet (Poeta sacer), a devotee who assumes the universal human destiny and whose task is to bear witness to and renew the covenant with the divine. By contrasting the Hyperborean essence of the poet with the heteronomy of contemporary material barbarism, Matić’s poetry simultaneously affirms the principle of Personality, increasingly endangered by the homogenization of values, dehumanization, and dechristianization of the world. The significance of returning to the ancient heritage—understood as the foundation of being, sacred knowledge, and knowledge of the Logos, which is not acquired through the accumulation of data but through insight into the equality of the human with the divine—is further confirmed in numerous interviews where Matić articulated his autopoietic views. These reflections are crucial both for interpreting his poetry and for understanding his philosophical insights into the essence of poetry and of the world itself. The dialogical framework of Hyperborean Chronicle underscores two central ideas of Matić’s poetics: first, that poetry is primarily a dialogue with the world, whose essence lies in revealing Truth to the Other—that visible reality is but an image of our inner world; and second, that poetry is the chosen mediator between Man and Truth, whose essential purpose is a call to vigilance, to self-forgetting, and to the rediscovery of one’s divine nature.
Keywords: Branislav Matić; Hyperborean Chronicle; hyperborea; heteronomy; Poet; Béla Hamvas; ancient heritage; Personality